Metal-Catalyzed Decarboxylation of Oxaloacetic Acid Studied in Silico and in Vitro, Implications for Enzymatic and Prebiotic Catalysis - Sepulveda, C (Elsevier B.V., 2025)
During the decarboxylation of oxaloacetic acid (OAA), an α-keto acid that participates in the central metabolic pathways of all organisms, its fourth carbon is released in the form of CO2 through a metal-catalyzed reaction. In the context of prebiotic chemistry, it is generally accepted that metalloenzymes catalyse reactions that could have originally occurred abiotically mediated by metals. In this study, we investigate the effect of various divalent cations (Ni2+, Co2+, Mn2+ and Mg2+) on the non-enzymatic decarboxylation rate of oxaloacetic acid (OAA) using both in silico quantum mechanical calculations and in vitro experimental analysis. Our experimental findings demonstrate that for the rate of OAA decarboxylation, the cations followed the order Ni2+ > Co2+ > Mg2+ > Mn2+. Theoretical results, utilizing the enolpyruvate metal complex as the final stage of the reaction, showed that the Ni2+ complex had the lowest decarboxylation energy and negative Gibbs free energy compared to other complexes. Additionally, it exhibited a lower HOMO-LUMO gap, indicating its potential to aid in the decarboxylation reaction. Given that decarboxylases in current metabolism primarily employ Mg2+ and Mn2+ but not Ni2+, we consider how the cation that performs better in the abiotic reaction was not selected as the catalytic centre of the enzyme-based reaction in current biochemistry. © 2024